TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PEMALSUAN SURAT PADA SELEKSI CALON PEGAWAI NEGERI SIPIL DI KABUPATEN TANA TORAJA ( Studi Kasus Putusan Nomor 38/Pid.B/2020/PN Mak ): JURIDICAL REVIEW ON THE CRIMINAL ACT OF CERTIFICATE FORMING ON THE SELECTION OF PROSPECTIVE CIVIL SERVANTS IN TANA TORAJA DISTRICT (Case Study Decision Number 38/Pid.B/2020/PN Mak) - Asdillah; Mas, Marwan; Zubaidah, Siti (Faculty Of Law Bosowa University, 2021)
This thesis aims to find out that the elements of letter forgery have been fulfilled in the decision No.38/Pid.B/2020/PN.Mak. and to find out the basis for the criminal decision of the Makale District Court No.38/Pid.B/2020/PN.Mak. in accordance with applicable law. This research uses normative legal research type. The types of data used are Primary Data and Secondary Data, data from primary legal materials in the form of court decisions and laws. Secondary legal materials refer to books, journals and other readings related to the problems being studied as well as sources of information obtained from interviews with the Panel of Judges to complete the required information. The results of this study indicate that it has been fulfilled and proven starting from elements 1) Whoever, 2) Deliberately participates in using a forged or forged letter as if it were true, if the use of the letter can cause harm. Based on the evidence of these elements, the defendants cannot avoid sanctions to account for the criminal acts committed. Then the basis for the criminal decision of the Makale District Court No.38/Pid.B/2020/PN Mak in deciding the case of the criminal act of forging letters is appropriate considering that the indictment is single. This can be seen based on the explanation of theastatements of the witnesses,athe statements of the accused, the evidence, as well as the existence of juridical considerations, mitigating matters and things that are aggravating the defendant, as well as paying attention to related laws which are strengthened by the judge's conviction.